Artificial Intelligence in Radiology: Current Technology and Future Directions - Syed, Ali B.; Zoga, Adam C. (Seminars in Musculoskeletal Radiology, 2018)
Artificial intelligence (AI) has been heralded as the next big wave in the computing revolution and touted as a transformative technology for many industries including health care. In radiology, considerable excitement and anxiety are associated with the promise of AI and its potential to disrupt the practice of the radiologist. Radiology has often served as the gateway for medical technological advancements, and AI will likely be no different. We present a brief overview of AI advancements that have driven recent interest, offer a review of the current literature, and examine the most likely ways that AI will change radiology in the coming years.
Keywords: artificial intelligence; machine learning; deep learning; radiology; informatics